PD-1/PD-L1 Axis Downregulation in Guillain-Barré Syndrome: A Potential Mechanism Driving the Autoimmune Pathogenesis - Mr Rasel Ahmed; Mrs Israt Jahan; Mrs Pritha Biswash; Miss Mehjabeen Haque; Miss Sarah Khurshid; Mr Jigishu Ahmed; Mr Sayed Akib Hossain; Dr Zhahirul Islam (International Journal of Infectious Diseases)
Introduction: Guillain-Barré syndrome (GBS), an immune-mediated disorder of the peripheral nervous system characterized by progressive muscle weakness, is often triggered by Campylobacter jejuni infection. Molecular mimicry between C. jejuni's lipo-oligosaccharides (LOS) and host nerve gangliosides likely initiates this heterogenic disorder. Besides microbial factors, the host's immune response may play a crucial role in GBS pathogenesis. The PD-1/PD-L1 pathway regulates T-cell differentiation, maintaining immune equilibrium. This study aims to compare PD-1/PD-L1 gene expression in GBS patients and healthy controls (HCs) and explore its correlation with regulatory/helper T-cell response in GBS. Methods: In this prospective study, 30 patients with GBS and 30 HCs were included. We isolated total RNA from peripheral blood mononuclear cells (PBMCs) and performed quantitative reverse transcription-polymerase chain reaction (RT-PCR) to assess PD-1/PD-L1 gene expression and analyzed via the 2−ΔΔCT method. Flow cytometry was performed to measure the regulatory T cells (Tregs) and helper-T-17 cells using CD4, CD25, FoxP3, and IL-17 antibodies. Mann-Whitney t-tests and simple linear regression were done to compare the PD-1/PD-L1 gene expression and their correlation with T-cell subsets. Results: In this cohort, the median age of GBS patients was 31 years (IQR:18-43), where 22 patients were male. Twenty-one patients were reported with antecedent events, primarily diarrhea (n=10), followed by fever (n=6), and common cold (n=5). Twenty-seven patients experienced severe clinical symptoms with a GBS-disability score ≥3, among them 14 required mechanical ventilation and 10 exhibited autonomic dysfunction. A significant downregulation of PD-1 (median difference = 0.5135, p = 0.0001) and PD-L1 (median difference= 0.5812, p< 0.0001) was found in patients with GBS compared to HCs. CD4+CD25+ Tregs (6.16% vs. 8.232%; p= 0.007) and CD4+CD25+FoxP3+ Tregs (3.21% vs. 4.508%; p= 0.015) were significantly reduced in acute GBS, whereas Th17 cells elevated in acute phase (p= 0.044) compared to HCs. Correlation analysis revealed that decreased relative expression of PD-1 (r, p= 0.503, 0.003 and r, p= 0.334, 0.015) and PD-L1 (r, p= 0.352, 0.020 and r, p= 0.306, 0.021) was associated with lower levels of CD4+CD25+FoxP3+ Tregs in GBS. However, no correlation was found between the regulation of PD-1/PD-L1 gene expression and Th17 cell levels in GBS. Discussion: This study highlights the downregulation of the PD-1/PD-L1 gene is involved in breaching of immune homeostasis by reducing CD4+CD25+FoxP3+ regulatory-T cells. This aligned with prior research, which hinted that PD-1/PD-L1′s influences on immune tolerance and plays a potential role in autoimmune diseases via Treg function regulation. Further investigation with a larger sample size with different time points is warranted to confirm the significance of PD-1/PD-L1 gene expression in the disease progression of GBS patients. Conclusion: In summary, the study suggests that decreased expression of PD-1/PD-L1 genes influences the expression of regulatory T-cells, potentially initiating autoimmunity in GBS.